Anchoring and traffic effects in the virtual market platform of FIFA 20 - Popescu, Andrei; Fiedler, Klaus (Journal of dynamic decision making, 2023)
An Internet-based competitive marketing game, FIFA 20, served to investigate the effectiveness of two opposite strategies in soccer-player auctions under semi-naturalistic conditions. Granting the validity of both causal principles, the anchoring principle giving an advantage to starting with a high price (Ritov, 1996) and the traffic principle underlying the starting-low advantage (Ku, Galinsky, & Murnighan, 2006), we nevertheless expected starting low strategies to produce higher end-prices under FIFA 20 conditions. Two experiments, each using multiple copies of two players from the lowest price segment (Kramaric, Pizzi) and from an elevated price segment (Laporte, Martial), corroborated these expectations. A starting-low advantage was evident in two utility aspects, enhanced average (profit) and reduced variance (uncertainty aversion) of end prices obtained for player copies offered at lower starting prices. However, when the causal impact of the manipulated starting value was overshadowed by extraneous media influences, these findings were reduced or disappeared but never reversed.